A Critical Hermeneutics Analysis of CEO/Chairman Letters written to Shareholders of Shoprite Holdings - Madakana, Sinazo (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
This research is a critical analysis of Shoprite's annual reports particularly CEO/Chairman letters written to shareholders during and after the apartheid era. This paper aims at studying business communication at specific historical junctures using the critical hermeneutics. This is done to uncover the symbolic meaning in business communication which serves the interests of the socially and political powerful. Also, this paper will investigate the usefulness of the CEO/Chairman letters and examine if they give a true and fair view of the company or they are just a rhetorical tool used to convince stakeholders.
Keywords: Psychology -- South Africa; Shoprite (Firm : -- South Africa) -- History; Corporation reports -- South Africa; Psychology -- Qualitative research; Hermeneutics; Critical discourse analysis; Corporations -- Investor relations -- South Africa; Corporate culture; Systematic review